The fast forward MBA in finance - Tracy, John A. (Portable MBA series., 1996)
The Fast Forward MBA in Finance shows you how to find the crucial numbers and make the most of them. Working within the framework of the financial statement, Tracy clearly explains how to use key financial and accounting tools and techniques to cut to the quick of all your crucial finance-related business problems.